MODEL FOR EDUCATIONAL INSTITUTION ADMINISTRATION BASED ON THE PRINCIPLES OF AESTHETIC EDUCATION FOR PRIMARY SCHOOL UNDER THE OFFICE OF PHRA NAKHON SI AYUTTHAYA PRIMARY EDUCATIONAL SERVICE AREA - Chamnianpan, Karantarat; Thitavaddhano, PhramahaYannawat; Jongsakulsiri, Padet (Journal of Bovorn Multi-Education and Human Social Sciences ( JOB_EHS ), 2025)
This research article aimed to propose a school administration model based on the principles of aesthetic education for primary schools under the Office of the Primary Educational Service Area of Phra Nakhon Si Ayutthaya. This research was a mixed-method research with 4 steps: Step 1: Studying the needs of school administration by using a questionnaire with a sample group of 354 administrators and teachers. Data were analyzed using statistics, namely percentage, mean, standard deviation, and PNI modified. Step 2: Developing the model by interviewing 16 key informants. The research instrument used was a semi-structured interview form. Data were analyzed using content analysis. Step 3: Testing the model by holding a small group meeting with 18 administrators, teachers, and school administrative supervisors. The research instrument used was a manual for using the model and an evaluation form for the opinions on the model. Data were analyzed using statistics to obtain the mean and standard deviation. Step 4: Evaluating the model by holding a focus group meeting with 9 experts. The research instrument used was a focus group discussion form. Data were analyzed using statistics, namely the mean and standard deviation. The results of the research found that the school administration model based on the principles of aesthetic education for primary schools under the Office of the Primary Educational Service Area, Phra Nakhon Si Ayutthaya, consisting of 1) Principles, 2) Objectives, 3) Integration of school administration with the principles of educational aesthetics in 3 aspects: satisfaction, ethics, volunteerism, 4) Application, 5) Trial use, 6) Evaluation. The results of the trial of the school administration model based on the principles of educational aesthetics which the opinions on the model were at the highest level. And the results of the evaluation of the school administration model based on the principles of educational aesthetics were at the highest level. Therefore, the knowledge was summarized as "BESE".